2009
DOI: 10.1002/cbic.200900321
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Binding to Amyloid‐β: Coordination, Dynamics, Aggregation, Reactivity and Metal‐Ion Transfer

Abstract: The metal ions copper, zinc and iron have been shown to be involved in Alzheimer's disease (AD). Cu, Zn and Fe ions are proposed to be implicated in two key steps of AD pathology: 1) aggregation of the peptide amyloid-beta (Abeta), and 2) production of reactive oxygen species (ROS) induced by Abeta. There is compelling evidence that Cu and Zn bind directly to Abeta in AD. This formation of Cu/Zn-Abeta complexes is thought to be aberrant as they have been detected only in AD, but not under healthy conditions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
285
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(302 citation statements)
references
References 94 publications
(123 reference statements)
9
285
1
1
Order By: Relevance
“…The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37). Thus, the affinities of L2-b for Cu 2þ and Zn 2þ at the relevant pHs [for metal-induced Aβ aggregation (2-4, 7-9)] suggest that this compound is able to chelate metal ions from soluble Aβ species, which could support the results from reactivity studies of L2-b with metal-treated Aβ species (vide infra).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37). Thus, the affinities of L2-b for Cu 2þ and Zn 2þ at the relevant pHs [for metal-induced Aβ aggregation (2-4, 7-9)] suggest that this compound is able to chelate metal ions from soluble Aβ species, which could support the results from reactivity studies of L2-b with metal-treated Aβ species (vide infra).…”
Section: Resultsmentioning
confidence: 63%
“…In addition to Aβ aggregate deposits, dyshomeostasis and miscompartmentalization of metal ions such as Fe, Cu, and Zn ions clearly occur in AD brains (1)(2)(3)(4)(6)(7)(8)(9)(10). Some studies suggest that highly concentrated metal ions play an important role in Aβ aggregate deposition and neurotoxicity including the formation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ) (1-4, 6-13).…”
mentioning
confidence: 99%
“…As such, Cu 2+ ‐enhanced reaction between mutant Aβs and between wt‐Aβ and post‐translationally modified Aβ might boost oligomer “seed” formation (the rate‐limiting step for fibril formation). Both copper‐bound Aβ monomer and copper‐bridged Aβ dimer have been proposed to be the intermediates towards aggregation 32, 33, 42, 43, 44. In order to unequivocally establish the oligomerisation mechanism in the presence of metal ions, Aβ peptides labelled with pairs of fluorophores would be necessary for the identification of co‐existing Aβ species.…”
Section: Resultsmentioning
confidence: 99%
“…According to the docking results, EGCG had a tendency to associate with Aβ primarily near the hydrophilic N-terminus and the α-helical region spanning residues H13 to D23 (46). This binding pocket is near the H6, H13, and H14 residues that may be responsible for metal binding to Aβ, as well as to residues in the hydrophobic self-recognition sequence, suggested to be linked to Aβ aggregation pathways (1,3,8,(47)(48)(49). A combination of polar (e.g., hydrogen bonding, electrostatic interaction) and hydrophobic interactions was likely responsible for the close proximity of EGCG to hydrophilic and hydrophobic portions of Aβ in solution.…”
Section: Molecular Modeling Studies Present That Egcg Could Interact mentioning
confidence: 99%